- Edukasi Peran Pajak Dalam Pembangunan Nasional Indonesia: Dalam Kegiatan Santunan di Babelan Bekasi : - - Sumarno Manrejo; Markonah Markonah; Yohanes Ferry Cahaya (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
This study aims to improve public understanding of the importance of taxes as a primary source of funding for national development. This is based on data showing the low level of tax awareness and literacy among the public, particularly in the Babelan area of ​​Bekasi, which results in suboptimal tax compliance. The method used in this study is a qualitative approach with participatory education through assistance activities. This activity combines the provision of social assistance with direct tax education to the public. Educational materials cover the function of taxes, the benefits of taxes for infrastructure development, education, and social welfare, as well as the importance of the community's role as taxpayers. The results show that an educational approach based on social activities, such as assistance, is effective in increasing public understanding and awareness of the role of taxes. The public becomes more open and enthusiastic in receiving tax information because it is delivered in a humanistic and contextual atmosphere. In addition, this activity also strengthens the relationship between educational institutions and the community. The results of this study indicate that integrating social activities with tax education can be an effective strategy in improving public tax literacy and compliance. Therefore, it is recommended that similar programs be replicated sustainably in other regions by involving various stakeholders to support the optimization of tax revenue and the smooth running of Indonesia's national development.